Effects of protein supplementation on body composition, physiological adaptations, and performance during endurance training: a systematic review and meta-analysis - Xiao, Yang; Deng, ZhengWu; Sun, Wei; Li, JiaYi; Gao, WeiFeng (Frontiers in Nutrition, 2025)
IntroductionThis study aimed to evaluate the long-term effects of endurance training combined with protein supplementation on body composition, physiological adaptations (aerobic/anaerobic capacity), and performance.MethodsA systematic search was conducted in Web of Science, PubMed, and SPORTDiscus databases on April 16, 2025, using the keywords “endurance training” and “protein supplementation.” Meta-analysis was conducted using a random-effects model, and the main effect size of each outcome was summarized using the standard mean difference (SMD), and moderators were explored using subgroup and regression analyses.ResultsA total of 23 randomized cross-over trials involving 1,146 participants were included. The results showed that protein supplementation during endurance training led to a small, nonsignificant increase in lean body mass (SMD = 0.13, 95% CI: −0.01, 0.28; p = 0.07) and a significant improvement in time to exhaustion (TTE) during endurance exercise (SMD = 0.45, 95% CI: 0.15, 0.76; p < 0.01). While the overall impact on maximal oxygen uptake (VO2max) was not significant, subgroup analysis revealed that untrained individuals may experience greater improvements in VO2max with protein supplementation (SMD = 0.21). Although aerobic and anaerobic capacities were assessed, protein supplementation did not lead to significant changes in these outcomes, nor did it significantly affect body weight or body fat.DiscussionIn summary, protein supplementation during endurance training appears to modestly enhance endurance performance (TTE) and may offer small benefits for lean body mass, particularly in untrained individuals. However, it does not significantly affect overall body weight, fat mass, or aerobic/anaerobic capacity in the general population.Systematic review registrationIdentifier, CRD420251034453, https://www.crd.york.ac.uk/PROSPERO/recorddashboard.